2021
DOI: 10.1088/1757-899x/1149/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Study for the Stress Analysis to Evaluate Single Lap Adhesive Joint

Abstract: The use of adhesive bonding is increased in load-bearing applications in place of conventional joining techniques such as bolted or rivets joints. The high-stress concentration occurs at the end of an adhesive-bonded lap joint so all failures begin at the end of the overlap region and get fractured in the end. The single-lap adhesive-bonded joint was used in the current study to examine the peel stress and shear stress results along the overlap region. The comparison of the analytical and experimental result w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Single-lap adhesive joints offer many benefits, such as saving time, economising on costs, very high strength and good damping properties in comparison with other conventional joining processes [1,2]. Ahmed and Tehami [3] and Gültekin et al [4] showed that bond length, adhesive thickness, adherend thickness, curing conditions and joint end geometry are the factors that affect the strength of the adhesive joints.…”
Section: Introductionmentioning
confidence: 99%
“…Single-lap adhesive joints offer many benefits, such as saving time, economising on costs, very high strength and good damping properties in comparison with other conventional joining processes [1,2]. Ahmed and Tehami [3] and Gültekin et al [4] showed that bond length, adhesive thickness, adherend thickness, curing conditions and joint end geometry are the factors that affect the strength of the adhesive joints.…”
Section: Introductionmentioning
confidence: 99%